Pengaruh pemberian asi eksklusif dan non eksklusif terhadap mental emosional anak usia 3-4 tahun - Setyarini, Any; Mexitalia, Maria; Margawati, Ani (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2015)
Background: Breastmilk is the best food contains all the elements of required nutrients for infant aged 0-6 months, and the attachment of the breastfeeding process give better of growth and mental emotional development of the infant. Less attachment between mother and infant caused mental emotional disorders, that affect to the next period of child’s development..Objective : The objective of this research was to analyze the differences of influence of exclusive breastfeeding and non exclusive brestfeeding history on child’s emotional mental age of 3-4 years as well as analyze the most dominant variables. Method: This was an observational analitic research with cross sectional approach. The subjects consisted of 84 children aged 3-4 years, living Banyumanik subdistrict Semarang, taken by purposive sampling and grouped into exclusive and non-exclusive breastfeeding. The data was collected by questionnaire, and the analysis using chi square and logistic regression.Result: The study showed that most of children with exclusively breastfed had good mental emotional (76.2%), while children who did not get exclusively breastfed had a mental emotional problem (64.3%). There were relations between breastfeeding (p=0,001), mother’s knowledge (p=0,001), mother’s attitude (p=0,001), and mother’s education level (p=0,029) to children’s mental emotional. Education level of mother was the most influence variable for child’s emotional mental after addjusted with mother’s knowledge, mother’s attitude, mother’s education level, and birth weight of children.Conclusion: Breastfeeding history, mother’s knowledge, mother’s attitude, and mother’s education level were factors that influencing to children’s mental emotional